New devices for measuring forces on the kayak foot bar and on the seat during flat-water kayak paddling: a technical report - Nilsson, J. E.; Rosdahl, H. G. (International Journal of Sports Physiology and Performance, 2014)
The purpose was to develop and validate portable force-measurement devices for recording push and pull forces applied by each foot to the foot bar of a kayak and the horizontal force at the seat. A foot plate on a single-point force transducer mounted on the kayak foot bar underneath each foot allowed the push and pull forces to be recorded. Two metal frames interconnected with 4 linear ball bearings, and a force transducer allowed recording of horizontal seat force. The foot-bar-force device was calibrated by loading each foot plate with weights in the push-pull direction perpendicular to the foot plate surface, while the seat-force device was calibrated to horizontal forces with and without weights on the seat. A strong linearity (r2 = .99-1.0) was found between transducer output signal and load force in the push and pull directions for both foot-bar transducers perpendicular to the foot plate and the seat-force-measuring device. Reliability of both devices was tested by means of a test-retest design. The coefficient of variation (CV) for foot-bar push and pull forces ranged from 0.1% to 1.1%, and the CV for the seat forces varied from 0.6% to 2.2%. The current study opens up a field for new investigations of the forces generated in the kayak and ways to optimize kayak-paddling performance.